2007
DOI: 10.1074/jbc.m702573200
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Regulates Hepatocyte Growth Factor-mediated Vascular Integrity

Abstract: The preservation of vascular endothelial cell (EC) barrier integrity is critical to normal vessel homeostasis, with barrier dysfunction being a feature of inflammation, tumor angiogenesis, atherosclerosis, and acute lung injury. Therefore, agents that preserve or restore vascular integrity have important therapeutic implications. In this study, we explored the regulation of hepatocyte growth factor (HGF)-mediated enhancement of EC barrier function via CD44 isoforms. We observed that HGF promoted c-Met associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 73 publications
(100 reference statements)
0
38
0
Order By: Relevance
“…There is no evidence, to our knowledge, of a direct interaction between Met and NHEs; however, there is evidence that Met may induce NHE activity through a, yet to be defined, tyrosine kinase-calcium/calmodulin-dependent mechanism (Kaneko et al, 1995). In addition, it is possible that CD44, the cell-surface receptor for hyaluronan, is involved, as both Met and NHEs have been shown to interact with CD44 (Bourguignon et al, 2004;Orian-Rousseau et al, 2002;Singleton et al, 2007). It would be interesting to determine if Met, CD44 (specifically the v6 splice variant), and NHEs interact and if the calcium/calmodulin pathway is involved in lysosome trafficking.…”
Section: Discussionmentioning
confidence: 93%
“…There is no evidence, to our knowledge, of a direct interaction between Met and NHEs; however, there is evidence that Met may induce NHE activity through a, yet to be defined, tyrosine kinase-calcium/calmodulin-dependent mechanism (Kaneko et al, 1995). In addition, it is possible that CD44, the cell-surface receptor for hyaluronan, is involved, as both Met and NHEs have been shown to interact with CD44 (Bourguignon et al, 2004;Orian-Rousseau et al, 2002;Singleton et al, 2007). It would be interesting to determine if Met, CD44 (specifically the v6 splice variant), and NHEs interact and if the calcium/calmodulin pathway is involved in lysosome trafficking.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies show that these cholesterol-enriched detergentresistant membrane microdomains play an important role in formylmethionylleucylphenylalanine-, phorbol myristate acetate-, Fc␥-, and angiotensin II-induced activation of NADPH oxidase by triggering the recruitment of key NADPH oxidase subunits (2,17,18). We have demonstrated that CEMs are critical for Rac1 activation of barrier-enhancing stimuli, including hyaluronan and hepatocyte growth factor (14,15). Hepatocyte growth factor-induced Rac1 activation requires recruitment of the vesicular regulator, dynamin 2, to CEM (15).…”
Section: P40mentioning
confidence: 99%
“…We have demonstrated that CEMs are critical for Rac1 activation of barrier-enhancing stimuli, including hyaluronan and hepatocyte growth factor (14,15). Hepatocyte growth factor-induced Rac1 activation requires recruitment of the vesicular regulator, dynamin 2, to CEM (15). In addition, caveolin-1 is essential for the activation of Rac1 and NADPH oxidase after angiotensin II stimulation of vascular smooth muscle cells (17).…”
Section: P40mentioning
confidence: 99%
“…Earlier studies indicated that CD44 can function as a co-receptor to activate the signaling pathway through interacting with several growth factor receptors. [26][27][28] It is possible that CD44 functions as a co-receptor to potentiate the growth signaling in mast cells. As c-kit is the dominant receptor that regulates proliferation and differentiation of mast cells, c-kit is one of the possible partners of CD44 when it functions as a co-receptor.…”
Section: Mechanism Underlying Cd44-mediated Proliferationmentioning
confidence: 99%